2010
DOI: 10.1111/j.1750-3841.2010.01614.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antibacterial Activities on Foodborne Pathogens of Artocarpus heterophyllus Lam. (Moraceae) Leaves Extracts

Abstract: Total water extract, ethyl acetate, and aqueous fractions from the leaves of Artocarpus heterophyllus were evaluated for phenolic content, antioxidant, and antibacterial activities against some foodborne pathogens such as E. coli, Listeria monocytogenes, Salmonella typhimurium, Salmonella enterica, Bacillus cereus, Enterococcus faecalis, and Staphylococcus aureus. The minimum inhibitory concentration (MICs) of extract and fractions determined by the agar dilution method were ranged from 221.9 microg/mL for eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 37 publications
3
60
0
3
Order By: Relevance
“…A large number of phenolic compounds including flavonoids, stilbenoids, and 2-arylbenzofurons have been isolated from Artocarpus plants and possess a wide range of biological properties such as anti-inflammatory (Hsu et al, 2012;Lin et al, 2011), antiplatelet (Jagtap & Bapat, 2010;Weng et al, 2006), antimycobacterial (Loizzo et al, 2010;Siritapetawee et al, 2012), and antiprotozoal activities (Bourjot et al, 2010). Among these activities, the antioxidant actions of these polyphenols derived from Artocarpus species have been frequently reported in vivo and in vitro (Omar et al, 2011;Sidahmed et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of phenolic compounds including flavonoids, stilbenoids, and 2-arylbenzofurons have been isolated from Artocarpus plants and possess a wide range of biological properties such as anti-inflammatory (Hsu et al, 2012;Lin et al, 2011), antiplatelet (Jagtap & Bapat, 2010;Weng et al, 2006), antimycobacterial (Loizzo et al, 2010;Siritapetawee et al, 2012), and antiprotozoal activities (Bourjot et al, 2010). Among these activities, the antioxidant actions of these polyphenols derived from Artocarpus species have been frequently reported in vivo and in vitro (Omar et al, 2011;Sidahmed et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The size of jackfruit seeds is extremely large. There are ∼100-500 seeds in the fruit representing 8-15% of the total fruit weight [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Food-borne illnesses associated with Listeria monocytogenes, Staphylococcus aureus, Escherichia coli O157:H7 and Salmonella enteritidis present a major public health concern [2,3]. It has been reported that the incidence of food-borne diseases caused by microbial contamination and environmental pollution will globally increase [4,5]. Furthermore, the consumption of foods contaminated with pathogenic microorganisms, such as bacteria, mould, viruses and parasites active the growth of a pathogen.…”
Section: Introductionmentioning
confidence: 99%